1,5-Diaza-3,7-diphosphacyclooctanes (P2N2): An Underappreciated Ligand Class for Nickel- and Palladium-Catalyzed Heck-Type Cross-Couplings - Isbrandt, Eric S.; Newman, Stephen G. (Synlett, 2024)
1,5-Diaza-3,7-diphosphacyclooctane (P2N2) scaffolds represent a readily accessible, tunable ligand class for transition metals. However, despite their prevalence in areas such as electrocatalysis and coordination chemistry, P2N2 ligands have been rarely used to make catalysts for organic synthesis. Research into Mizoroki–Heck-type aldehyde, alcohol, and alkene arylation reactions has revealed that the P2N2 family outperforms many commonly used phosphines. This Synpacts article summarizes our work and provides a broad overview on the preparation and application of P2N2 ligands in organic synthesis. It also serves to highlight how a simple, modular class of ligands can solve contemporary challenges with transition-metal catalysis, including novel reactivity and exceptional regioselectivity.
Keywords: transition-metal catalysis; Mizoroki–Heck coupling; ligand design; regioselectivity; reductive cross-coupling